Sports Massage Training and Injury Repositioning Students of Yapis Timika Vocational School - Herwin, Herwin; Trisakti, Jhon Citro; Nurwirhanuddin, Nurwirhanuddin; Suprianto, Suprianto; Letisia, Maria; Siga, Adolfus Siktus; Renyaan, Anastasya; Umafagur, Dea Andela (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Sports massage is a form of massage therapy designed to accelerate recovery and improve the performance of athletes and non-athletes who engage in various physical activities. Sports massage can be given to children, adolescents, and adults, including workers, students, and college students. Sports massage is not only for athletes but can also be given to students to prevent and hinder injuries during the learning process at school. It can also provide first aid if a fellow student experiences an injury, whether during extracurricular or extracurricular activities.This community service program aims to provide education about sports massage and injury repositioning to students and teachers involved in extracurricular activities, thereby fostering independence in helping fellow students in the event of injuries and enabling teachers to provide professional services to their students. Furthermore, this PKM activity, as an implementation of the sports massage course in the community, involves students who have completed the theory/practice of sports massage courses.The data collection technique used in this Community Service (PKM) was an evaluation method, conducted by administering a participant satisfaction questionnaire after the training was completed. The questionnaire was administered online using the Google Forms platform to participants in the sports massage and injury repositioning training. In addition to data on student and teacher/extracurricular instructor satisfaction indicators, physical evidence also included documentation from before, during, and after the training.The data were analyzed using descriptive methods. Based on the results of the evaluation, it shows that from the training activities that have been given to students of SMK Yapis Timika from a total of 18 students, it was found that 82.6% of students strongly agree, students agree 14.7%, students quite agree 2.7%. Meanwhile, the results of the evaluation that followed the training showed that from the training activities that have been given to teachers/extracurricular instructors of SMK Yapis Timika from the number of teachers/extracurricular instructors who participated in this activity 1 person, it was found that 70% of teachers/extracurricular instructors strongly agree, teachers/extracurricular instructors agree 25%, teachers/extracurricular instructors quite agree 5%.